Noninterventional Therapies for the Management of Knee Osteoarthritis - Dadabo, Joseph; Fram, Julia; Jayabalan, Prakash (The Journal of Knee Surgery, 2019)
The goal of the practitioner managing a patient with knee osteoarthritis (OA) is to minimize pain and optimize their function. Several noninterventional (noninjectable) therapies are available for these individuals, each having varying levels of efficacy. An individualized approach to the patient is most beneficial in individuals with knee OA and the treatment plan the practitioner chooses should be based on this principle. The focus of this article is to provide an up-to-date overview of the treatment strategies available, evidence to support them, and in whom these treatments would be most appropriate. These include exercise (aerobic and resistance), weight loss, bracing and orthotics, topical and oral analgesic medications, therapeutic modalities, and oral supplements.
Keywords: knee osteoarthritis; exercise; modalities; pain